Ameliorative effect of synthesized silver nanoparticles by green route method from Zingiber zerumbet on mycoplasmal pneumonia in experimental mice. Issue 1 (4th December 2019) - Yang, Yong; Song, Wenping; Chen, Zongbo; Li, Qiubo; Liu, Li
Abstract: Mycoplasma pneumoniae (MP) can infect both the upper and lower respiratory tracts related diseases and a common cause of community-acquired pneumonia, mostly in young children and adolescents. Zingiber zerumbet (L.) belongs to the family of Zingiberaceae and it is a perennial and aromatic plant that cultivates in subtropical and tropical countries. This plant is traditionally found throughout Southeast Asia and the Pacific region, where it is commonly used in foods, and beverages purposes. Zingiber zerumbet is a valuable foundation of diverse classes of bioactive major compounds that fit to a varied diversity of chemical metabolites, including polyphenols, alkaloids and terpenes. The numerous studies of Z. zerumbet have shown the enormous pharmacological potential of this plant and its derived bioactive compounds in the treatment of various immune-related diseases like inflammation and other chronic diseases. Based on the previous scientific reports, there are no scientific investigations that claim the antipneumonial activity of the Z. zerumbet based silver nanoparticle. Therefore, the aim of the present study was designed and evaluated the anti-pneumonial potential of biosynthesized with Z. zerumbet based silver nanoparticles in mycoplasmal pneumonia in experimental rats.